GAMERIK Simulation Model Improves Students’ Computer Assembly Skills: Model Simulasi GAMERIK Meningkatkan Keterampilan Perakitan Komputer Siswa - Nuryadi, Adi; Darmawan, Deni; Rahadian, Dian; Nurjamin, Asep; Jamilah, Jamilah; Maulani, Galih Abdul Fatah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Practical technical learning such as computer assembly often faces challenges due to low student motivation and limited practice facilities. Specific Background: At SMAN 2 Garut, conventional methods have proven less effective in improving computer assembly skills. Knowledge Gap: Few gamification-based simulation learning models have been tested to significantly enhance technical skills. Aims: This study aims to develop and evaluate the effectiveness of the GAMERIK (Gamification of Computer Assembly) learning model using the PC Creator 2 simulation to improve Grade X students’ computer assembly skills. Results: Using an R&D approach with the ADDIE model, data were collected through observation, questionnaires, interviews, pretests, and posttests. A paired sample t-test showed a significant increase in students’ motivation, conceptual understanding, and assembly skills (p < 0.05). Novelty: The integration of PC Creator 2’s automated assessment algorithm within the gamification model provided immediate feedback, accelerating the learning process. Implications: GAMERIK offers an innovative solution for practice-based learning in schools with limited facilities and is relevant to the development of simulation- and gamification-based informatics learning media. Highlights: Enhances motivation and skills in technical learning. Uses simulation with automated assessment for feedback. Offers solutions for schools with limited practice facilities. Keywords: GAMERIK, Gamification, PC Creator 2, Computer Assembly Skills, Simulation